Assessment of hysteroscopic role in management of women with recurrent pregnancy loss. (3rd June 2018) - Elsokkary, M.; Elshourbagy, M.; Labib, K.; Mamdouh, A.; El-Shahawy, Y.; Nossair, Wael S.; Abd El Fattah, O.; Hemeda, H.; Sallam, S.; Khalaf, Waleed M.; Ali, M.; Elsayed, M.; et al.
Abstract: Objectives: To assess the hysteroscopic value in the management of intrauterine lesion in women with recurrent pregnancy loss. Methods: This study was done in Ain Shams Maternity Hospital after the approval of the research Ethics Committee, during the period between August 2014 and December 2015 where 200 nonpregnant women with a history of three or more consecutive unexplained first and second trimester miscarriages before 20 weeks were recruited from recurrent miscarriage clinic. A written informed consent was obtained from all women before participation. Results: This current study was conducted in Ain Shams University Maternity Hospital during the period between August 2014 to May 2015 a total of 200 women with history of recurrent miscarriage were included in the study. Regarding the results of this study the mean age was 30.5(5.7), the mean number of previous abortion 3(3–5) the mean number of the first trimesteric abortion was 2 with range (2–2) the mean number of second trimesteric abortion was 2 with range (1–2). In this study, 88% of patients were nullipara. It was also found that hysteroscopic findings were found in 58.5%. Uterine anomalies was present in 21%, including septate uterus and intrauterine adhesion (IUAs) were present in 12.5%. Endometrial polyps were present in 8.5%, bicornute uterus in 4.5%, unicornuate uterus in 4.5% while submucous myomas were present in 7.5%. It was found that 48.5% need hysteroscopic intervention including 21% need septectomy 12.5% need adhesiolysis, 6.5% need myomectomy while 8.5% need polypectomy. The study found that no statistically significant difference between patients with normal hysteroscopic finding and patients with abnormal hysteroscopic finding as regard age, time of previous abortion and number of previous abortion. But there was statistically significant difference as regard number of previous delivery and abnormal HSG. Conclusions: It appears that hysteroscopy is a useful tool in the diagnosis and treatment of the causes of recurrent miscarriage that can be performed safely without anesthesia in most cases. The prevalence of uterine anomalies in patients with recurrent miscarriages is 54.5%, septate uterus is the most common anomaly and for this reason uterine anomalies should be systematically assessed in patients with recurrent miscarriage.